2002
DOI: 10.1289/ehp.021101113
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls alter extraneuronal but not tissue dopamine concentrations in adult rat striatum: an in vivo microdialysis study.

Abstract: Polychlorinated biphenyls (PCBs) reduce tissue dopamine (DA) concentrations and increase media DA concentrations in both in vitro preparations of bovine adrenal chromaffin cells and adult rat striatal tissue. To determine whether these changes also occur in the intact animal, we used in vivo microdialysis to determine changes in concentrations of DA in striatal dialysates from freely moving adult male rats after exposure to 25 mg/kg/day Aroclor 1254 for varying periods of time. We also determined DA concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 35 publications
3
43
1
1
Order By: Relevance
“…The mechanisms of PCB neurotoxicity most likely involve multiple modes of action, which largely depend upon the congener structure. The mechanisms include effects on thyroid hormone dependent neurodevelopment (Zoeller et al, 2002); binding to and activation of the aryl hydrocarbon receptor (AhR) by planar PCBs by a mechanism similar to that of dioxin (Collins et al, 2008;Powers et al, 2005); impairment of the function of glutamate-nitric oxide-cGMP pathway (Piedrafita et al, 14 2008); effects on brain cholinergic muscarinic receptors (Coccini et al, 2006); and damage to dopaminergic neurons (Seegal et al, 2002). In our study, CB-153 (a PCB congener with a non-planar structure) was the most abundant PCB congener in CSF and cerebellum GM.…”
Section: Pcb and Pcb Metabolitesmentioning
confidence: 99%
“…The mechanisms of PCB neurotoxicity most likely involve multiple modes of action, which largely depend upon the congener structure. The mechanisms include effects on thyroid hormone dependent neurodevelopment (Zoeller et al, 2002); binding to and activation of the aryl hydrocarbon receptor (AhR) by planar PCBs by a mechanism similar to that of dioxin (Collins et al, 2008;Powers et al, 2005); impairment of the function of glutamate-nitric oxide-cGMP pathway (Piedrafita et al, 14 2008); effects on brain cholinergic muscarinic receptors (Coccini et al, 2006); and damage to dopaminergic neurons (Seegal et al, 2002). In our study, CB-153 (a PCB congener with a non-planar structure) was the most abundant PCB congener in CSF and cerebellum GM.…”
Section: Pcb and Pcb Metabolitesmentioning
confidence: 99%
“…Results from in vivo rat studies have shown that adult PCB exposure alters extra-neuronal DA concentrations (Seegal et al, 2002), and eventually reduces the levels of frontal cortical and striatal DA (Seegal et al, 1997). Other studies, in both adult non-human primates and rats exposed to PCBs for several weeks, revealed a reduction in the number of tyrosine hydroxylase positive (TH + ) DA neurons in the substantia nigra (SN) (Seegal, Chishti, and Brosch, unpublished observations).…”
Section: Introductionmentioning
confidence: 98%
“…Previously, PCBs and their metabolites were shown to impact neurotransmitter and steroid hormone systems underlying reproductive function (Khan and Thomas, 2001;Ptak et al, 2005;Seegal et al, 1985;Seegal et al, 2002;Tsai et al, 1997). These changes in turn are likely to have profound effects on reproductive behaviors.…”
Section: Introductionmentioning
confidence: 99%